Can hysteroscopy be substituted to hysterosalpingography in the assessment of infertility? Methods of showing tubal transition as hysteroscopic - Buket Aydın Yanar; Eren Pek; Mesut A. Unsal (Clinical and Experimental Obstetrics & Gynecology)
Background: The main goal of this study was to prove that hysteroscopy is a superior method compared to hysterosalpingography in the evaluation of tubal passage and the uterine cavity in infertile women. Methods: The study was carried out on 30 volunteer women for whom evaluation of the uterine cavity and transit through the tubules was required due to infertility. In the evaluation of the hysteroscopic tubal passage, a 6Fr feeding cannula was advanced from the hysteroscope barrel, and firstly methylene blue and then an air bubble were applied to the fluid-filled uterine cavity through this flexible cannula. Results: When the reference method was taken as hysterosalpingography, the specificity of hysteroscopy was found to be 85.71% (95% CI (confidence interval): 42.13%–99.64%), sensitivity 94.74% (95% CI: 85.38–98.90%). The positive predictive value of hysteroscopy was calculated as 98.18% (95% CI: 89.78%–99.70%) and the negative predictive value was 66.67% (95% CI: 38.96%–86.24%). Observing the bubble and swirl effect together in the evaluation of the tube opening increases the diagnostic accuracy. And benefit of hysteroscopy in the evaluation of tubal passage was statistically significantly higher than hysterosalpingography. Conclusion: Considering the cellular damages that can be caused by hysterosalpingraphy and the real observation power provided by hysteroscopy, simultaneous evaluation and the comfort of making intervention possible, hysteroscopy will be a more useful and useful application.